Relations between theory of mind and academic school readiness: the moderating role of child gender - Martins, C.; Barreto, A.; Baptista, J.; Osório, A.; Martins, E.; Verissimo, M. (Merrill-Palmer Quarterly, 2019)
This study investigated the prospective relationship between preschoolers’ theory of mind (ToM) skills and academic school readiness, while exploring the possible moderator role played by child gender. The participants were 75 children who were assessed at two time points: when enrolled in the second preschool year (T1) and again 4 months before school entry (T2). The results showed an association between children's ToM abilities at T1 (but not at T2) and later academic readiness at T2, but only for girls, even after accounting for child IQ and maternal education. These findings support the idea that girls and boys can differ in how they use their ToM abilities in their daily life and highlight the relevance of further exploring gender-specific effects when investigating children's social cognition and school readiness.